CLIL TEACHERS’ PERCEPTIONS OF INTERCULTURAL COMPETENCE IN PRIMARY EDUCATION - Pérez Gracia, Elisa (2017)
CLIL (Content and Language Integrated Learning) includes the development of intercultural awareness as one of its main axes. Therefore, the main objective of this research is to examine the perceptions that CLIL teachers have regarding Intercultural Competence (IC) and the elements that contribute to its development. Through an open-question survey, we analysed the opinions of 59 Primary Education CLIL teachers from Cordoba. For the analysis of the qualitative data, Atlas.ti has been used on its two options: the textual and the conceptual analysis, thus generating the corresponding networks. On the other hand, SPSS v. 21 was used for the quantitative data analysis. The results show that CLIL teachers define IC closely linked to linguistic competence, and that communicative activities play an important role.